Treatment Patterns, Outcomes, and Costs Associated With Localized Upper Tract Urothelial Carcinoma. Issue 6 (1st October 2021) - Fero, Katherine E; Shan, Yong; Lec, Patrick M; Sharma, Vidit; Srinivasan, Aditya; Movva, Giri; Baillargeon, Jacques; Chamie, Karim; Williams, Stephen B
Abstract: Background: Upper tract urothelial carcinoma (UTUC) is a heterogeneous disease that presents a clinical management challenge for the urologic surgeon. We assessed treatment patterns, costs, and survival outcomes among patients with nonmetastatic UTUC. Methods: We identified 4114 patients diagnosed with nonmetastatic UTUC from 2004 to 2013 in the Survival Epidemiology, and End Results–Medicare population-based database. Patients were stratified into low- or high-risk disease groups. Median total costs from 30 days prior to diagnosis through 365 days after diagnosis were compared between groups. Overall and cancer-specific survival were evaluated using Cox proportional hazards regression. All statistical tests were 2-sided. Results: After risk stratification, 1027 (24.9%) and 3087 (75.0%) patients were classified into low- vs high-risk UTUC groups. Most patients underwent at least 1 surgical intervention (95.1%); 68.4% underwent at least 1 endoscopic intervention. Patients diagnosed with high- vs low-risk UTUC were more likely to undergo nephroureterectomy (83.6% vs 72.0%; P  <   .001); few patients with low-risk disease were exclusively managed endoscopically (16.9%). At 365 days after diagnosis, costs of care for high- vs low-risk UTUC were statistically significantly higher ($108 520 vs $91 233; median difference $16 704, 95% confidence interval [CI] = $11 619 to $21 778; P  <   .001). Those with high-risk UTUC had worse cancer-specific and overall survival compared with patients with low-risk UTUC (cancer-specific survival hazard ratio [HR] = 4.14, 95% CI = 3.19 to 5.37; overall survival HR = 1.78, 95% CI = 1.62 to 1.96). Conclusions: UTUC continues to be managed primarily with nephroureterectomy, regardless of risk stratification, and patients with high-risk UTUC have worse overall and cancer-specific survival. Substantial costs are associated with management of low- and high-risk UTUC, with the latter being more costly up to 1 year from diagnosis.